Evaluating inductive vs deductive research in management studies: Implications for authors, editors, and reviewers. Issue 2 (11th June 2018) - Woiceshyn, Jaana; Daellenbach, Urs
Abstract : Purpose: The purpose of this paper is to address the imbalance between inductive and deductive research in management and organizational studies and to suggest changes in the journal review and publishing process that would help correct the imbalance by encouraging more inductive research. Design/methodology/approach: The authors briefly review the ongoing debate about the "developmental" vs "as-is/light-touch" journal review modes, trace the roots of the prevailing developmental review to the hypothetico-deductive research approach, and contrast publishing deductive and inductive research from the perspectives of authors, editors, and reviewers. Findings: Application of the same developmental evaluation and review mode to both deductive and inductive research, despite their fundamental differences, discourages inductive research. The authors argue that a light-touch review is more appropriate for inductive research, given its different logic. Practical implications: Specific criteria for the light-touch evaluation and review of and some concrete suggestions for facilitating inductive research. Social implications: Advancing knowledge requires a better balance of inductive and deductive research, which can be facilitated by light-touch evaluation and review of inductive research. Originality/value: Building on the debate on journal publishing, the authors differentiate the evaluation and review of inductive and deductive research based on their philosophical underpinnings and draw implications of pursuing inductive research for authors, editors, and reviewers.